Qualitative Evaluation of RFID Implementation on Warehouse Management System - Syafrial Fachri Pane; Rolly Maulana Awangga; Bayu Rahmad Azhari (Universitas Ahmad Dahlan, 2018)
Logistic sector actors need innovation to improve competitiveness in providing their best services to consumers, one of them on Warehouse Management System (WMS) because the system is used to control the movement of the supply chain. There is a problem in one of Indonesia logistics companies on the process of selecting goods, so the warehouseman still difficulties in this process. Thus, RFID implementation on WMS becomes one of the solutions to handle the goods selection process. This research uses Design Science Research Methodology (DSRM) which focuses on developing and improving the model performance of a system and using waterfall model for system development. Then the authors will analyze the test results with the validity test and reliability test of the questionnaire, and the results of the data analysis will determine the feasibility of this research to be applied.